A comparative study on the television program preferences of the male and female high school students in the urban and rural areas - Freires, Tiffany S.; Somcio, Hygeia C.; Tolouie, Mozhgan T. (1996.)
The study is about the TV program preferences of males and female high school students in the rural and urban areas. The objectives are: (1) to compare the TV program preferences of the male and female students in the rural and urban areas; (2) to know whether there is a significant difference in their choices; and (3) to identify the reasons why they watch such programs. , There were thirty-five (35) female and thirty-five (35) male respondents from Oton national High School which represent the rural area. Thirty-five (35) male and thirty-seven (37) female respondents came from Iloilo National High School which represents the urban area. A questionnaire was utilized to get the TV program preferences of the high school students. (p)The results show that the male students of Oton National High School preferred X-men, Baywatch, Star Cinema, Power Rangers and Million dollar Movies. The male students of Iloilo National High School chose Power Rangers, Baywatch, Million Dollar Movies, X-men and Rescue 911. The choices of the female respondents of Oton National High School are Star Cinema, Baywatch, Star Drama Presents, Power Rangers and The Sharon Cuneta Show. The female respondents of Iloilo National High School chose the following shows: Baywatch, Power Rangers, Star Cinema, Star Drama Presents and The Sharon Cuneta Show. The respondents reasons for watching the show are: (a) "it is their show"; (b) "their favorite actor/actresses are in the show"; (c) "it is interesting"; (d) "they can learn lessons from it" and (e) "that their family watches the show". (p)To indicate if there is a significant difference in their choices, the test on proportion was used with a .05 level of significance. It was found out that the choices of the males in the rural and urban areas do not have a significant difference. On the other hand, the choices of females of the rural and urban areas showed a significant difference.
Thesis (Undergraduate, Bachelor of Arts in Broadcast Communication-Psychology) College of Arts and Sciences, University of the Philippines in the Visayas, Miag-ao, Iloilo
Keywords: Students, High School -- Female -- Rural Areas; Students, High School -- Female -- Urban Areas; Students, High School -- Male -- Urban Areas; Students, High School -- Male -- Rural Areas